Reducing mother-to-child transmission of HIV in the Caribbean (CAREC Port -of-SpainTT, 1999)
Looks at the epidemiological profile and the treatment regimens. Makes suggestions for the implementation and evaluation of MTCT programmes, as well as the implementation of evaluation and specific operational studies. Provides recommendations.
Keywords: HIV